AUDIT KEAMANAN SISTEM INFORMASI: Berdasarkan SNI - ISO 27001 Pada Sistem Informasi Akademik Universitas Pembangunan Nasional "Veteran" Jakarta - Darma Yanto Putra, (2020)
ABSTRACT Darma Yanto Putra - 1610512074, Audit Keamanan Sistem Informasi Berdasarkan SNI - ISO 27001 Pada Sistem Informasi Akademik Universitas Pembangunan Nasional "Veteran Jakarta". Under the guidance of Theresiawati,S.Kom,MTI and I Wayan Widi P.,S.Kom.,MM. The occurrence of damage to information system assets, do not have information system security policy that must be applied in security also supervision of information academic service assets, the possibility of threat and risk against information system support. This research have a purpose to plan Information Security Management System (ISMS) with its use as guidelines of information system policy in UPT TIK UPN "Veteran" Jakarta. The main discussion in this research is Information Security Management System (ISMS) analysis using ISO/IEC 27001 to UPT TIK UPN "Veteran" Jakarta Information Academic System. This research using Plan, Do, Check, and Act methods in collecting, analyze, and processing data. The result of this research is maturity level of ISO 27001 with average located in level two, be expected this research would be helpfull to provide a recomendation to control information security as guidance and procedure for implementation of information security policy. Keywords: ISO 27001, Information Security Management System (ISMS), Plan, Do, Check, Act